The Economic Impact of a Renewable Biofuels/Energy Industry Supply Chain Using the Renewable Energy Economic Analysis Layers Modeling System - English, Burton C.; Menard, R. Jamey; Wilson, Bradly (Frontiers in Energy Research, 2022)
This analysis provides an example scenario to demonstrate the Renewable Energy Economic Analysis Layers (REEAL) modeling system’s analytical capabilities. The conversion technology modeled is a Gasification Fischer-Tropsch biorefinery with feedstock input of 495,000 metric tons per year of forest residue transported to a logging road that is less than one mile in distance. The biorefinery is expected to produce sustainable aviation fuel (SAF), diesel, and naphtha converting one million tons of forest residues at 50 percent moisture content. Based on a Technical Economic Assessment (TEA) developed by the Aviation Sustainable Center (ASCENT) and the quantity of hardwood residues available in the Central Appalachian region, three biorefineries could be sited. Each biorefinery could produce 47.5 million liters of SAF, 40.3 million liters of diesel, and 23.6 million liters of Naphtha. Annual gross revenues for fuel required for the biorefineries to breakeven are estimated at 193.7 million per biorefinery. Breakeven plant gate fuel prices when assuming RINS and 12.2 percent return on investment are 1.12 per liter for SAF, 1.15 per liter for diesel, and 0.97 per liter for naphtha. The estimated economic annual impact to the Central Appalachian Region if the three biorefineries are sited results in an estimated 2.67 billion in economic activity with a multiplier of 1.7, or for every million dollars spent, an additional 0.7 million in economic activity is generated in the regional economy. Gross regional product is estimated at 1.28 billion, employment of nearly 1,200 jobs are created during the construction period of the biorefineries, which results in 700 million in labor income with multiplier effects. Economic activity for the feedstock operations is estimated at slightly more than 16.8 million resulting in an additional 30 million in economic impacts. The stumpage payments occurring from the harvest of the forest residues results in 40 million directly to the resource and logging operation owners. Their subsequent expenditures resulted in total economic activity increase of 71.4 million creating an estimated 103 direct jobs. Transportation expenditures of more than 36.7 million provides an estimated increase in economic activity of almost 68 million accounting for the multiplier effects.